Studi Kinerja Protokol Routing Ad-Hoc On Demand Multipath Distance Vector (AOMDV) dalam Lingkup Vehicular Ad-Hoc Network (VANET) pada Daerah Perkotaan - Abraham Arya Satyana; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Vehicular Ad-hoc Network (VANET) is a network formed from many nodes that communicate with each other without any main network. To be able to communicate with each other, a process is needed to determine the path for information exchange. The process of determining the path of information exchange is called by routing. The number of nodes incorporated in the VANET network may cause a high routing load on the network. But it can be minimized, one of which is the multipath method. The Ad-hoc On Demand Multipath Distance Vector (AOMDV) protocol is one of the routing protocols that has a multipath method. The multipath method in the AOMDV protocol works by providing an alternative routing path that will be used if the main routing line is cuts off on its multipath mechanism. The performance of the AOMDV protocol can be determined based on testing of Quality of Service (QoS) parameters; Packet Delivery Ratio, End-to-end Delay, Normalized Routing Load, Overhead Routing, and Convergence Time. And based on the test results of the QoS parameters that have been tested, the AOMDV protocol runs optimally at a speed of about 75 km/h.